Pengembangan Sistem Informasi Pergudangan dan Penjualan Menggunakan Model Incremental Development pada CV Hook Fight Gear - Arva Abi Maulana; M. Sahrul Ramdani; Rifaldi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
CV Hook Fight Gear is a company engaged in the trading of boxing and martial arts equipment. Currently, the management of goods data and sales transactions is still carried out manually using notebooks and spreadsheets. Problems that arise include stock recording errors, difficulty in data searching, delays in report generation, and the absence of user access differentiation. This study aims to design and implement a Warehouse and Sales Information System based on Python to improve the company’s operational efficiency. The system was developed using the Incremental Development Model with Python technology, CustomTkinter for the user interface, and SQLite as the database. Implementation results show that the system successfully integrates modules for goods data, cashier transactions, warehousing, and automatic reporting. Black box testing on 17 scenarios resulted in valid status for all tests. This system is able to reduce recording errors and accelerate business processes at CV Hook Fight Gear.